ANALISIS KEMAMPUAN PEMECAHAN MASALAH UNTUK SETIAP TAHAP MODEL POLYA DARI SISWASMK IBU PAKUSARI JURUSAN MULTIMEDIA PADAPOKOK BAHASAN PROGRAM LINIER - Ninik, N; Hobri, H; Suharto, S (KadikmA, 2014)
Abstract.Problem solving abilityshould be trainedandtaughtbyteacher to a vocational studentwhois preparedtoplungeintothe world of work. One effortto trainstudentsproblem solving abilityisPolyaâsmodel. Polyamodelconsistsoffour stages:understanding theproblem, makingthe completion ofthe plan, implementthe plan, andre-examine. The purposeof this study is todetermine the problem solving ability of SMK IbuPakusariâs multimedia studentson the subject oflinear program. Data collection methodusedis the method oftesting, interviews, anddocumentation. From the researchit can be concludedthat the percentage of students in problem solving ability is high, medium, low on stage to understand the problem is75%, 12,5%, 12,5%. For the percentage of students on stage the completion ofthe plan is 40,63%, 18,75% ,40,62%. On stage implementthe plan is 46,87%, 18,75%, 34,38%. As for the re-examine is 37,5%, 34,38%, 28,12%. Key Words : Polyaâs Model, Problem solving ability, linear program